Intention to Do Whistleblowing in Government Institutions:An Experimental Study - Muhammad IKBAL (Management and Economics Review, 2017)
This study aims to examine the effect of the provided reporting channels on intention of individuals to disclose fraud actions (whistleblowing), moderated by rewards and guaranteed protection. The approach used is an experiment by assigning graduate students in public sector financial management as participants. The results show that although reporting channels were provided, they did not automatically make individuals whistleblowing even if when reward was provided, it did not significantly affect individuals’ whistleblowing. However, when a treatment was given on the experimental model by providing a guarantee of protection for whistleblowers, it was seen that there was significant effect on the strong intention from individuals whistleblowing, the implication of this study is the importance of protection for whistleblowers, so that the disclosure of fraud will be more effective.